Question about Computers & Internet

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

The x intercept is where your line will cross the x axis. Therefore, the value for y at this point is 0. Substitute 0 for y in this equation and solve for x.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

6x + 3(0) = 27

x = 27/6

x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27

y = 27/3

y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

May 18, 2012 | SoftMath Algebrator - Algebra Homework...

This is very basic scientific calculator and you cannot use it with variables.

As to your equation (if you want to solve it) it is much simpler to do so with pen and paper.

Write it as

3y-6=-7y +4

Take the 6 from the left to the right where it becomes +6, Thus

3y=-7y+4+6

3y=-7y+10

Take the -7y term from the right to the left side, where it becomes +7y

3y+7y=10 or 10y=10.

The solution is clearly y=1.

As to your equation (if you want to solve it) it is much simpler to do so with pen and paper.

Write it as

3y-6=-7y +4

Take the 6 from the left to the right where it becomes +6, Thus

3y=-7y+4+6

3y=-7y+10

Take the -7y term from the right to the left side, where it becomes +7y

3y+7y=10 or 10y=10.

The solution is clearly y=1.

Mar 03, 2010 | Texas Instruments TI-30XA Calculator

You can solve it with following method.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

5x+3y=6 2x-4y=5

So 5x=6-3y so 2[(6-3y)/5]-4y=5

So x=(6-3y)/5 so 12-6y-20y=25

so -26y=25-12

so -26y=13

so y= -(1/2)

2x-4y=5

so 2x=5+4y

so 2x=5+4(-1/2)

so 2x=(10-4)/2

so 2x=6/4

so x =3/2

The value of x=3/2 and value of y= -1/2

Let me know if you need further assistance.

Thanks for using FixYa.

Mar 03, 2010 | Office Equipment & Supplies

I am sorry to be the messenger with bad news, but this calculator does not do symbolic algebra. It does not have a solve function either.

You do have 5 memory variables in which you can store numerical values but it will not do you any good in this particular case.

Anyway, there is nothing you can do with such an expression (IT IS NOT an equation, just an expression) , except some cosmetic change 2x(2x-3y) or expand it 4x^2-6xy.

You do have 5 memory variables in which you can store numerical values but it will not do you any good in this particular case.

Anyway, there is nothing you can do with such an expression (IT IS NOT an equation, just an expression) , except some cosmetic change 2x(2x-3y) or expand it 4x^2-6xy.

Feb 11, 2010 | Texas Instruments TI-34II Explorer Plus...

The two numbers are 9 and 27.

Solution:

Suppose the two numbers are x and y, then,

x + y = 36 ---------1

and

x = 3y -------------2

Solving equation 1 and 2...

3y+y=36 => 4y=36 => y = 9

x + 9 = 36 => x = 27

Please rate and comment if my answer is right.

Solution:

Suppose the two numbers are x and y, then,

x + y = 36 ---------1

and

x = 3y -------------2

Solving equation 1 and 2...

3y+y=36 => 4y=36 => y = 9

x + 9 = 36 => x = 27

Please rate and comment if my answer is right.

Jan 31, 2010 | SoftMath Algebrator - Algebra Homework...

2y - x = 3

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is**x = 1**, **y = 2**

or in ordered pair notation**(1, 2)**

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is

or in ordered pair notation

Jun 29, 2009 | Computers & Internet

(x+3y=0)*3=3x+9y

y=1 x= -3

y=1 x= -3

Jun 29, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

Mode>choose "5"

choose equation format "4"

input the coefficient for a which is "1" and hit "="

input the coefficient for b which is "4" and hit "="

input the coefficient for c which is "3" and hit "="

input the coefficient for d which is "12" and hit "="

Hit "=" for X1

Hit "=" again for X2

Hit "=" again for X3

choose equation format "4"

input the coefficient for a which is "1" and hit "="

input the coefficient for b which is "4" and hit "="

input the coefficient for c which is "3" and hit "="

input the coefficient for d which is "12" and hit "="

Hit "=" for X1

Hit "=" again for X2

Hit "=" again for X3

Nov 18, 2007 | Casio Office Equipment & Supplies

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

98 people viewed this question

Usually answered in minutes!

×